AKTIVITAS ANTIMIKROBA BAKTERI ASAM LAKTAT DARI AIR SUSU IBU (ASI) TERHADAP Listeria monocytogenes FNCC 0156 - Antari, Made Juli; Puspawati, Ni Nyoman; Wipradnyadewi, Putu Ari Sandhi (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 1 (2020): Jurnal ITEPA, 2020)
The aim of the research was to find the potency of Lactic Acid Bacteria isolated from breast milk on inhibiting Listeria monocytogenes FNCC 0156 and to find the magnitude of lactic acid bacteria from breast milk in inhibiting L. monocytogenes FNCC 0156. This reseach consists of two phase: antimicrobial activity of lactic acid bacteria from breast milk and activity of bacteriocin against L. monocytogenes FNCC 0156. Isolate used in this research was A1, A3, A6, A8, A9, B3, B7, B8, and B10b. Antimicrobial activity of lactic acid bacteria from breast milk against L. monocytogenes FNCC 0156 was performed cell free supernatant, cell free neutral supernatant, and cell free neutral heated supernatant. The test was performed by well-agar diffusion method and contact method. The activity of bacteriocin was carried out according to the optimum incubation time of bacteriocin production in cell free heated neutral supernatant. The highest antimicrobial activity was supernatant treatment by well-agar diffusion method and contact method showed by isolate A1 with inhibition diameter of 10.60 mm and a decrease of 1.66 log cycle. The highest antimicrobial activity was neutral supernatant treatment by well-agar diffusion method and contact method showed by isolate B8 with inhibition diameter of 5.11 mm and increased only by 0.18 log cycle. The highest antimicrobial activity on the heated neutral supernatant treatment by well-agar diffusion method and contact method showed by isolate A6 with inhibition diameter of 0.85 mm and a decrease of 0.48 log cycle. The two isolates of cell free neutral heated supernatant treatment was isolate A6 and isolate B8 suspected to have bacteriocin compounds was then continued with isolation of bacteriocin. The result of the second phase showed that optimum time for bacteriocin production of isolate A6 was 36 hours and B8 was 60 hours. The highest antimicrobial activity of bacteriocin was showen by isolate A6 with an average inhibition diameter of 5.36 mm, followed by B8 with an average inhibition diameter of 2.44 mm. Keywords: lactic acid bacteria, breast milk, Listeria monocytogenes FNCC 0156, antimicrobial activity, bacteriocin